2019
DOI: 10.1111/jvim.15537
|View full text |Cite
|
Sign up to set email alerts
|

Association of acuteBabesia canisinfection and serum lipid, lipoprotein, and apoprotein concentrations in dogs

Abstract: Background Babesia canis infection induces a marked acute phase response (APR) that might be associated with alteration in lipid and lipoprotein metabolism and disease prognosis. Hypothesis Dogs with B. canis ‐induced APR develop dyslipidemia with altered lipoprotein concentration and morphology. Animals Twenty‐nine client‐owned dogs with acute B. canis infection and 10 clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
3
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
1
15
3
2
Order By: Relevance
“…However, patients infected with Babesia display lipid abnormalities and markedly low HDL levels, suggesting these parasites depend on host lipid metabolism as well ( Cunha et al, 2000 ; Bock et al, 2017 ; Table 1 ). Similar abnormalities have been observed in Babesia -infected cattle and canines ( Goodger et al, 1990 ; Milanović et al, 2019 ). These parasites have been demonstrated to rewire lipid biosynthesis to produce PC during the blood stage, much like Plasmodium ( Florin-Christensen et al, 2000 ).…”
Section: Intracellular Growthsupporting
confidence: 80%
“…However, patients infected with Babesia display lipid abnormalities and markedly low HDL levels, suggesting these parasites depend on host lipid metabolism as well ( Cunha et al, 2000 ; Bock et al, 2017 ; Table 1 ). Similar abnormalities have been observed in Babesia -infected cattle and canines ( Goodger et al, 1990 ; Milanović et al, 2019 ). These parasites have been demonstrated to rewire lipid biosynthesis to produce PC during the blood stage, much like Plasmodium ( Florin-Christensen et al, 2000 ).…”
Section: Intracellular Growthsupporting
confidence: 80%
“…Apo-A1 has been recently measured in a group of dogs with leishmaniosis, which had significantly decreased serum concentrations of this protein compared to healthy controls; furthermore, dogs with a good response to anti-Leishmania treatment displayed a significant increase of Apo-A1, suggesting its role as a potential biomarker of treatment monitoring during this disease (5). Curiously, Milanović et al reported a parallel Apo-A1 and SAA serum concentration increase in a population of dogs with acute infection by Babesia canis compared to control dogs; however, the latter finding is still unexplained and warrants further assessment (6).…”
Section: Introductionmentioning
confidence: 99%
“…infection, large Babesia forms in the blood smears and positive PCR test for B. canis. Dogs were not included if proven positive for the modifi ed Knott test or had visible wounds, diagnosed allergy, endocrinopathies or neoplasms [19]. Complete blood count (CBC) was performed at presentation and dogs received the fi rst dose of imidocarb-dipropionate (6 mg/kg of body weight, s.c.).…”
Section: Animalsmentioning
confidence: 99%